The Effects of Website Traits and Medical Skepticism on Patients' Willingness to Follow Web-Based Medical Advice: Web-Based Experiment - Jennifer Claggett; Brent Kitchens; Maria Paino; Kaitlyn Beisecker Levin (JMIR Publications, 2022)
BackgroundAs people increasingly turn to web-based sources for medical information, we offer some insight into what website traits influence patients' credibility assessment. Specifically, we control for brand and content length, while manipulating three website traits: authorship, format, and tone. Furthermore, we focus on medical skepticism to understand how patients with high levels of medical skepticism may react to web-based medical information differently. Medical skepticism is related to a patient's doubts about the value of conventional medical care; therefore, skeptics may have different practices and criteria when conducting their own web-based medical searches. ObjectiveThe aim of this study is to evaluate how website traits affect the likelihood that patients follow web-based medical advice and how this varies among patients with differing levels of medical skepticism. MethodsThis web-based experiment presented participants with a hypothetical medical situation about leg cramps and offered a website with treatment advice. We varied the websites the participants observed across three traits: authorship (patient or physician), format (article or discussion forum), and tone (objective or experience-based). The 2305 participants were randomly assigned to 1 of 8 possible conditions and then asked the extent to which they would follow the advice. Health care patterns and coverage, demographics, and the participants' level of medical skepticism were captured. ResultsOur participants were selected to be demographically representative of the population of internet users in the United States. The 2305 complete responses were analyzed with ordinary least squares regression. Our analysis reveals that people are more likely to accept web-based medical advice authored by a physician (P<.001) and presented with an objective tone (P=.006), but these preferences erode as the levels of medical skepticism increase. Medical skepticism was measured by means of a previously established index on a 0 to 4 scale, and the average score was 2.26 (SD 0.84). Individuals with higher levels of medical skepticism were more likely to follow web-based medical advice in our experiment (P<.001). Individuals with low levels of medical skepticism found the discussion forum format more credible, whereas those with high levels of medical skepticism preferred the article format (P=.03). We discuss the interactions between medical skepticism and all 3 website traits manipulated in the experiment. ConclusionsOur findings suggest that, generally, physician authorship and an objective tone create more persuasive web-based medical advice. However, there are differences in how patients with high levels of medical skepticism react to web-based medical resources. Medical skeptics are less discerning regarding the author's credentials and the presentation tone of the information. Furthermore, patients with higher levels of medical skepticism prefer article format presentations, whereas those with lower levels of medical skepticism prefer discussion forum-style formatting.